THE INFLUENCE OF CAREER ANXIETY ON PSYCHOLOGICAL WELL-BEING OF UNIVERSITY STUDENTS FINAL LEVEL - Vidatul Qamariyah; Nuzulul Khair (Living Sufism: Journal of Sufism and Psychotherapy, 2024)
Career anxiety is a common phenomenon experienced by final-year students as they transition from education to the workforce. This anxiety can lead to psychological issues if not balanced with proper career preparation. If the quality of their psychological well-being is low, they are more likely to experience negative feelings such as stress, depression, and anxiety, including career-related anxiety. Therefore, this study aims to investigate the influence of career anxiety on the psychological well-being of final-year students at Universitas Annuqayah Guluk-Guluk Sumenep in 2024. The research employs a quantitative approach with a non-experimental correlational design. It is based on two main theories: Caroll Ryff's theory of psychological well-being and Tsai et al.'s theory of career anxiety. Data collection methods include interviews and Likert scale instruments distributed both online and offline to 30 randomly selected final-year students. The measurement tools used are the career anxiety scale and the psychological well-being scale. Data analysis results indicate a significance value (Sig.) of 0.424 > 0.05, which means there is no significant influence of career anxiety on the psychological well-being of final-year students at Universitas Annuqayah in 2024. The contribution of career anxiety to psychological well-being is minimal, at only 2.3%. This finding supports the notion that other factors play a more dominant role in influencing the psychological well-being of final-year students at Universitas Annuqayah.